Literature survey: The potential of integrating immersive experience and aesthetic experience in virtual reality historical event - Mohd Ekram Al Hafis Hashim (Tanjong Malim, 2024)
Literature survey: The potential of integrating immersive experience and aesthetic experience in virtual reality historical event by Mohd Ekram Al Hafis Hashim